The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.11606/d.22.2001.tde-19022003-171830
|View full text |Cite
|
Sign up to set email alerts
|

O tratamento supervisionado no controle da tuberculose em Ribeirão Preto sob a percepção do doente.

Abstract: Villa (TITE). Agradeço a acolhida que tive desde o início desta caminhada, a orientação e estímulo que me fizeram crescer como ser humano e profissional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
9

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 10 publications
(12 reference statements)
2
7
0
9
Order By: Relevance
“…In fact, the interviews revealed that almost all professionals accompanying patients or who were responsible for ST in the health unit belonged to the nursing team. This fact was identified in other studies carried out in Ribeirão Preto and in the West and Central regions of the city of São Paulo (9,(11)(12)(13) .…”
Section: Rev Esc Enfermsupporting
confidence: 69%
See 4 more Smart Citations
“…In fact, the interviews revealed that almost all professionals accompanying patients or who were responsible for ST in the health unit belonged to the nursing team. This fact was identified in other studies carried out in Ribeirão Preto and in the West and Central regions of the city of São Paulo (9,(11)(12)(13) .…”
Section: Rev Esc Enfermsupporting
confidence: 69%
“…The results found in this study are in agreement with that of others concerning the fact that there are patients who do not even mention the word Tuberculosis (thing) and do not accept the diagnosis. It reflects the perseverance of stigma and discrimination (9)(10)(11)(12) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations